ANALISIS MATERI PENDIDIKAN AGAMA ISLAM DALAM MENJAWAB TANTANGAN MORAL GENERASI Z - Sabrun Jamil; Indika Yahsifa; Fariha As'ad; Sella Herlanda; Wiranda; Ahmad Husnil Mubarak; Maisyarah (STKIP Subang, 2026)
This study analyzes Islamic Education (PAI) material in addressing the moral challenges faced by Generation Z in the modern digital era. The research is motivated by the increasing moral degradation among youth influenced by globalization, technological advancement, and the shift in value systems. The main objective is to examine how PAI materials in school curricula can respond to these moral challenges and contribute to the formation of noble character. This descriptive qualitative study employs library research as its primary method, utilizing books, journals, and related scientific articles as data sources. The data were analyzed through content analysis by identifying, classifying, and interpreting the moral values embedded within the PAI learning materials. The findings show that PAI materials still possess strong potential to strengthen students’ moral reasoning, particularly by emphasizing prophetic values such as honesty, responsibility, empathy, and social awareness. However, the integration of these values into the learning process remains limited and often less adaptive to the digital habits of Generation Z. The study concludes that revitalizing PAI material with contextual approaches, including digital-based learning and contemporary moral case studies, is essential to make moral education more relatable and effective for today’s youth.